Analysis Of Consumer Protection Laws Against Food And Beverage Products That Do Not Have Halal Labels In Gorontalo City - Nofrianto Harun (Universitas Negeri Gorontalo, 2019)
This study aims to find out and analyze how consumer protection against food and beverage products that do not have halal labels in Gorontalo City and to find out and analyze what factors cause there are still many circulating food and beverages not labeled halal in Gorontalo city. The type of research used is empirical and juridical legal research and uses qualitative data analysis techniques. The results showed that consumer protection of food and beverage products that do not have halal labels in Gorontalo City is still not well implemented this can be seen from the many food and drink products that are not labeled halal widely circulated and very much in Gorontalo city. As well as factors that cause there are still many circulating food and beverages not labeled halal in the city of Gorontalo, namely a) Convoluted economic and administrative factors, b) Business Factors undertaken are small businesses, c) The lack of public knowledge about law no. 33 of 2014 on halal product guarantees. Keywords: Consumer Protection, Halal Label, LPPOM-MUI